Randomized Trial Comparing Patient Comfort Between the Oral and Nasal Insertion Routes for Linear Endobronchial Ultrasound. Issue 1 (January 2016) - Beaudoin, Stéphane; Martel, Simon; Pelletier, Sabrina; Lampron, Noël; Simon, Mathieu; Laberge, Francis; Delage, Antoine
Abstract : Background: Linear endobronchial ultrasound (EBUS) is a safe and accurate sampling method for mediastinal adenopathy. The transnasal approach has been proposed to improve patient comfort, but no data compare the oral and nasal routes. The objective was to compare patient comfort during linear EBUS under conscious sedation between the oral and the nasal routes. Methods: An open-label randomized study comparing the 2 insertion routes for linear EBUS was conducted. Standardized protocols for sedation and topical anesthesia were used. Primary outcome was subjects' comfort measured by a 10-point scale filled 2 hours after the procedure. Willingness to return for a repeat examination, procedural characteristics, complications, and diagnostic yields were also compared. Results: A total of 220 subjects were randomized and allocated to the nasal (n=110) or oral (n=110) route. Twenty-seven subjects in the nasal group (24.5%) had a failed nasal insertion but were analyzed in the nasal group. Procedural characteristics were similar (EBUS duration, doses of sedatives and lidocaine, number of stations sampled, complications). There was no difference between the nasal and oral groups in subjects' comfort (8.3 vs. 8.3, respectively, P =0.99), overall patient satisfaction (8.9 vs. 9.1, respectively, P =0.34), subjects' willingness to return (96% vs. 97%, P =1.00), and physician-reported subject comfort. Rates of adequate specimens and diagnostic yields did not differ significantly between the groups. Conclusions: For linear EBUS, the nasal and oral approaches confer a similarly high degree of patient comfort with similar complication rates and diagnostic yield. Patient and physician preferences should dictate the route of insertion.